IMPLEMENTASI PERDA TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN DI KABUPATEN KUDUS - Fajar Heru Trihanggo; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
ABSTRACT The implementation of regional regulations on waste/cleanliness service retribution in Kudus Regency is an effort of the regional government to implement regional autonomy in the field of waste management. The regulation is the basis for the Kudus Regency regional government to manage local revenue and provide services to the community related to waste management. However, the services provided by the local government are only about 60% of the population served while the area of service provided is only 75% of the total area of Kudus Regency. The purpose of this study is to describe and analyze the implementation of local regulations on waste/cleanliness services retribution in Kudus Regency and to identify and analyze the factors that influence the implementation of local regulations on waste/cleanliness services retribution in Kudus Regency. The researcher uses an implementation model that the researcher collects with a top-down approach based on Van Meter and Van Horn theory. Factors that researchers use in discussing the implementation of the research under study are policy standards and objectives; policy resources; communication between implementing agencies; the attitude of the implementers; implementing agent characteristics; and social, political and economic conditions. The results showed that the implementation of local regulations on waste/cleanliness service retribution in Kudus Regency was not optimal due to the influence of regulatory clarity related to the difference in tariff between retribution groups, resulting in differences in understanding between implementing officers, tariff rates that were not in accordance with the economic conditions of the community, and lack of human resources and financial resources cause the services provided are still limited. Suggestions that the researchers can be given is to review retribution rates in accordance with the economic conditions of the community, increase cooperation with all village governments related to waste management, establish cooperation with private parties related to capital and increase public participation in participation as customers of waste service retribution.